The Perceptions of Teachers from Various Academic Levels of English Language In House Training: A Qualitative Study - Listyani; Martha Nandari; Victoria Usadya Palupi; Dimas Purnama Adi Wicaksono; Elisathusilawani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
An in house training program is a kind of training given to the staff or teachers of a company or a school. The training is adjusted with the needs of the staff or teachers and it is usually conducted by the institution or school. The purpose of in house training can be various. Commonly, the purpose is to improve the skills or knowledge of the staff or teachers. This research was conducted to see teachers’ perceptions on the implementation of in-house training held by a group of leading private schools in Central Java Indonesia, who were under the same institution. Facilitators in the training were lecturers from an English Education Study Programs. Research participants were 44 teachers from playgroup, primary school, and secondary school. Data were collected from an online questionnaire distributed at the end of the training in May 2024, using Google Form. Results showed that the majority of the teacher participants (95.45%) admitted that the training was necessary. Top two answers were that the program was necessary to improve the teachers’ skills in English, as well as to refresh their memory, mind, and knowledge about English.